Digital inclusive finance for green transformation: Insight from green innovation, industrial upgrading, and employment quality - Wulin Wu; Xiaowen Lin (Journal of Innovation & Knowledge)
Understanding the influence of digital inclusive finance (DIF) on inclusive green growth (IGG) is crucial for promoting the green transformation and sustainable development of developing economies. This study explores the effect of DIF on IGG in Chinese cities, and how DIF affects IGG by effectively coupling financial instruments with green transformation goals through a “triple mediation mechanism”. The findings reveal that DIF significantly promotes IGG, as well as economic growth, income distribution, welfare inclusiveness, and environmental protection. Furthermore, green technology innovation, industrial upgrading, and employment quality play a mediating role in the DIF-IGG relationship. Additionally, the main effect is stronger in the east and south, and cities with higher level of economic development, industrial upgrading, population density, agricultural entrepreneurship, and non-agricultural entrepreneurship, as well as in the 2016–2022 period. Overall, this study reveals the mechanisms and effects of DIF on IGG, expands the scope of research on economic green transformation, and provides new empirical evidence and valuable references for advancing financial sustainability and IGG in China and other developing countries. It also offers insights into addressing the current global ecological and environmental crises, and economic inequality.